Cardiovascular and Central Nervous System Effects of Co-administered Lidocaine and Bupivacaine in Piglets. Issue 2 (March 1991) - Kyttä, Juha; Badgwell, J. Michael; Heavner, James E.; Rosenberg, Per H.
Abstract : The toxic profile of bupivacaine (1 mg/kg/minute) when administered intravenously alone or with lidocaine (1 mg/kg loading dose, then 1 mg/kg/minute) was examined in 12 2-day-old pigs anesthetized with 70% N2 O/30% O2 and paralyzed with 0.15 mg/kg pancuronium. Bupivacaine doses producing arrhythmias, seizures, isoelectric EEG and asystole were about 24% lower in the lidocaine plus bupivacaine group ( n = 6) than in the bupivacaine group ( n = 6). However, the incidence of cardiac arrhythmias in the combination local anesthetic group (3/6) was half that in the bupivacaine group (6/6). Administration of lidocaine with bupivacaine under conditions of this study apparently reduces the risk of cardiac arrhythmias and acts along with bupivacaine to produce seizures, cerebral depression (isoelectric EEG) and asystole.